Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858121
|View full text |Cite
|
Sign up to set email alerts
|

Atelier

Abstract: Expert crowdsourcing marketplaces have untapped potential to empower workers' career and skill development. Currently, many workers cannot afford to invest the time and sacrifice the earnings required to learn a new skill, and a lack of experience makes it difficult to get job offers even if they do. In this paper, we seek to lower the threshold to skill development by repurposing existing tasks on the marketplace as mentored, paid, real-world work experiences, which we refer to as micro-internships. We instan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Recent research in crowdsourcing has introduced a variety of new interaction paradigms that enable non-experts to learn and perform complex, expert-level tasks [57,67,79]. The ideas and lessons learned have not yet made their way into citizen science or research-oriented crowdsourcing, suggesting many opportunities for future work.…”
Section: Open Questions For Cscw Researchersmentioning
confidence: 99%
“…Recent research in crowdsourcing has introduced a variety of new interaction paradigms that enable non-experts to learn and perform complex, expert-level tasks [57,67,79]. The ideas and lessons learned have not yet made their way into citizen science or research-oriented crowdsourcing, suggesting many opportunities for future work.…”
Section: Open Questions For Cscw Researchersmentioning
confidence: 99%
“…Instead, we hope that flash organizations will offer crowd workers, who are currently predominantly piecework employees, the opportunity to join longer-term and more fulfilling projects. More broadly, flash organizations help envision a world that enables crowd workers to pursue long-term careers [42], including skill growth [77], access to labor collectives [73], and guarantees of stable income.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work instead sought to achieve complex goals by moving from microtask workers to expert workers. Such systems now support user interface prototyping [70], questionanswering and debugging for software engineers [11,22,50], worker management [28,45], remote writing tasks [61], and skill training [77]. For example, flash teams demonstrated that expert workflows can achieve far more complex goals than can be accomplished using microtask workflows [70].…”
Section: Crowdsourcing Workflowsmentioning
confidence: 99%
“…The results are shown in Now we test the influence of skill number of tasks on the six types of performances of the five approaches. The scopes of skill number of tasks in the experiments are set as [5,10], [10][11][12][13][14][15], [15][16][17][18][19][20], [20][21][22][23][24][25]. The parameter of the relative importance factor α is set to 0.75.…”
Section: Tests On the Relative Importance Factormentioning
confidence: 99%
“…Compared with traditional task allocation, the advantages of crowdsourcing include faster completion speed [8], lower costs [9], higher accuracy [10], and completion of tasks that computers cannot perform [11]. There are many crowdsourcing platforms have been developed, such as Amazon's Mechanical Turk [12], UPwork [13], and MicroWorkERs [14].…”
Section: Introductionmentioning
confidence: 99%